Bandgap Funneling in Bismuth‐Based Hybrid Perovskite Photocatalyst with Efficient Visible‐Light‐Driven Hydrogen Evolution. Issue 8 (22nd June 2022) - Tang, Yunqi; Mak, Chun Hong; Wang, Chen; Fu, Yu; Li, Fang‐Fang; Jia, Guohua; Hsieh, Chang‐Wei; Shen, Hsin‐Hui; Colmenares, Juan Carlos; Song, Haisheng; Yuan, Mingjian; Chen, Yue; et al.
Abstract: The photocatalytic system using hydrohalic acid (HX) for hydrogen production is a promising strategy to generate clean and renewable fuels as well as value‐added chemicals (such as X2 /X3 − ). However, it is still challenging to develop a visible‐light active and strong‐acid resistive photocatalyst. Hybrid perovskites have been recognized as a potential photocatalyst for photovoltaic HX splitting. Herein, a novel environmentally friendly mixed halide perovskite MA3 Bi2 Cl9–x Ix with a bandgap funnel structure is developed, i.e., confirmed by energy dispersive X‐ray analysis and density functional theory calculations. Due to gradient neutral formation energy within iodine‐doped MA3 Bi2 Cl9, the concentration of iodide element decreases from the surface to the interior across the MA3 Bi2 Cl9–x Ix perovskite. Because of the aligned energy levels of iodide/chloride‐mixed MA3 Bi2 Cl9–x Ix, a graded bandgap funnel structure is therefore formed, leading to the promotion of photoinduced charge transfer from the interior to the surface for efficient photocatalytic redox reaction. As a result, the hydrogen generation rate of the optimized MA3 Bi2 Cl9–x Ix is enhanced up to ≈341 ± 61.7 µmol h −1 with a Pt co‐catalyst under visible light irradiation. Abstract : Bandgap funneling of lead‐free bismuth‐based perovskites MA3 Bi2 Cl9–x Ix provides an "energy staircase" for electrons and holes. The concentration of the iodide element decreases from the surface to the interior across the MA3 Bi2 Cl9–x Ix perovskite and forms an aligned energy level of iodide/chloride‐mixed MA3 Bi2 Cl9–x Ix, leading to the promotion of photoinduced charge transfer.